Functional impact of high clopidogrel maintenance dosing in patients undergoing elective percutaneous coronary interventions - Angiolillo, Dominick J; Bernardo, Esther; Palazuelos, Jorge; Desai, Bhaloo; Weisberg, Ian; Alfonso, Fernando; Guzman, Luis A; Hernández-Antolin, Rosana; Zenni, Martin Z; Macaya, Carlos; Fernandez-Ortiz, Antonio; Bass, Theodore A (Thrombosis and Haemostasis, 2008)
The currently recommended maintenance dose of clopidogrel is often associated with inadequate platelet inhibition, suggesting the need for a higher dose. The aim of this pilot study was to assess the functional impact of a high (150 mg/day) maintenance dose of clopidogrel in patients undergoing elective percutaneous coronary intervention (PCI).This is a prospective, randomized, platelet function study which was performed in elective PCI patients assigned to treatment with either a 75 mg (n=20) or 150 mg (n=20) daily maintenance dose of clopidogrel for 30 days;afterwards, all patients resumed standard dosing. Platelet aggregation was performed using light transmittance aggregometry following 20 μM and 5 μM adenosine diphosphate (ADP) stimuli 30 days after randomization and 30 days after resuming standard dosing. Patients treated with 150 mg/day clopidogrel had lower 20 μMADP-induced platelet aggregation compared to patients on 75 mg/day (52.1±9% vs. 64.0±8%; p<0.001; primary endpoint).The dose-dependent effect was confirmed by the absolute and relative increase in platelet aggregation after resuming standard dosing (p<0.001). No changes were observed in patients randomized to standard dosing. Parallel findings were observed following 5 μM ADP stimuli for all assessments. A broad variability in clopidogrel-induced antiplatelet effects was observed irrespective of dosing. In conclusion, a 150 mg/day maintenance dose regimen of clopidogrel is associated with reduced platelet reactivity and enhanced platelet inhibition compared to that achieved with the currently recommended 75 mg/day in patients undergoing elective PCI.
Keywords: Clopidogrel; platelet; coronary stenting